Centro de apoio e vivências para crianças e adolescentes com autismo em Palmas – TO - Silva, Caroline Alves da (Universidade Federal do Tocantins, 2021)
The present work aims to study children and adolescents who have autism, taking into account their interaction with the built environment. The specificities in which the disorder may entail will be objects of study for the conception of an architectural project proposal at the preliminary project level aiming at the composition of spaces prepared to receive and provide them with a good experience in therapies, consultations and experiences. The architecture in this study will have the function of optimize the experiences of treatments and social interactions with the patients, making accessibility guarantee them better daily interaction with the space around them, making a significant change in their life quality. The theory of sensory architecture will be used to make up spaces that are beyond clinical, comfortable and therapeutic, also a place of comfort and confidence in which children and adolescents feel comfortable to open up and adhere to treatments more easily. Thus, the proposal of the building aims at the well-being and social inclusion of these people and the breaking of barriers such as the tendency to isolation, communication difficulties and other behavioral characteristics.